Antagonistic Ghd7‐OsNAC42 Complexes Modulate Carbon and Nitrogen Metabolism to Achieves Superior Quality and High Yield in Rice - Guangming Lou; Pingli Chen; Pingbo Li; Haozhou Gao; Jiawang Xiong; Shanshan Wan; Yuanyuan Zheng; Yufu Wang; Mufid Alam; Yingnanjun Chen; Lei Wang; Jingjing Bai; et al. (Advanced Science)
Abstract Close coordination of carbon and nitrogen (C/N) metabolism is necessary to maintain optimal growth and development of plants and other cellular organisms. The central regulator for achieving high‐yield and quality synergy in rice through regulating the dynamic C/N balance has seldom been reported. Here, the novel function of Grain number, plant height, and heading date7 (Ghd7) gene are reported as both a negative regulator of grain protein content and a positive regulator of rice grain quality (including appearance quality and eating quality). As a transcription factor with both activating and inhibitory functions, Ghd7 directly binds to CCACC motif genes involved in C/N metabolism. OsNAC42, an interacting protein of Ghd7, antagonistically regulates the expression of these target genes in rice seedlings and endosperm by forming a heterodimer with Ghd7. The antagonistic Ghd7‐OsNAC42 module can flexibly regulate C/N metabolism in vivo in response to various nitrogen levels, thereby maintaining a dynamic C/N balance. Phenotypically, OsNAC42 enhances grain protein content but compromises quality‐functions opposing Ghd7's effects. In summary, the discovery of the Ghd7‐OsNAC42 antagonistic module provides new insights into the synergy between superior quality and high yield in rice.